Proceedings of the 34th International Cosmic Ray Conference — PoS(ICRC2015) 2016
DOI: 10.22323/1.236.0514
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Turbulent Magnetic Fields in Cosmic Ray Ansiotropy

Abstract: Cosmic ray anisotropy has been observed to be present in a wide energy range by a variety of experiments such as Milagro and the IceCube Observatory. However, a satisfactory explanation has been elusive for more than fifteen years now. A possible solution for the TeV-PeV cosmic ray anisotropy is the introduction of turbulent magnetic interactions on the arrival direction. We perform test particle simulations in compressible magnetohydrodynamic turbulence to study how cosmic rays' arrival direction distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Giacinti and Sigl (2012) also showed that these local magnetic field structures could create such anisotropies. Similar work to our code was calculated in López- Barquero et al (2015). However, that study primarily looked at particles with PeV-scale energies, where the Larmor radius and mean-free-path are on parsec scales, similar in size to the coherence length of the magnetic turbulence.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Giacinti and Sigl (2012) also showed that these local magnetic field structures could create such anisotropies. Similar work to our code was calculated in López- Barquero et al (2015). However, that study primarily looked at particles with PeV-scale energies, where the Larmor radius and mean-free-path are on parsec scales, similar in size to the coherence length of the magnetic turbulence.…”
Section: Discussionmentioning
confidence: 90%
“…Full MC integration of these TeV particles is intractably slow, so this was why a hybrid diffusion+MC method was needed. Additionally, López-Barquero et al (2015) assumed that the source population was diffuse, which allowed them to timereverse incoming particles to get maps of the anisotropic sky. However, our code allows for general source distributions in which particular CR sources are dominating the anisotropy.…”
Section: Discussionmentioning
confidence: 99%
“…The new understanding of the statistics and dynamics of turbulent magnetic fields can shed light on some long-standing problems and observational puzzles (e.g., Palmer, 1982;Evoli and Yan, 2014;López-Barquero et al, 2016;Krumholz et al, 2020;Xu, 2021). It was found that the numerically tested model of MHD turbulence, rather than isotropic Kolmogorov turbulence, can satisfactorily interpret the high-precision AMS-02 measurements of CRs (Fornieri et al, 2021).…”
Section: Interactions Of Crs With Mhd Turbulencementioning
confidence: 99%